Influence of Absorbing Material Distribution on Double Slope Sound Decay in L-Shaped Room - MEISSNER, Mirosław (Archives of Acoustics, 2008)
The sound decay process in L-shaped room was the subject of this investigation. The room with walls covered by the low absorbent material constituted the initial configuration for the study. To decrease a reverberation time, alterations of acoustic room properties were carried out by adding a high absorbent material on lateral room walls. Two different material configurations were considered and their effects on a double slope sound decay were analysed. In order to predict the behaviour of decay curve, a numerical implementation based on the wave theory was applied. A space distribution of eigenfunctions was computed using the forced oscillator method with a finite difference algorithm. Numerical results have demonstrated that an introduction of high absorbent material on selected room walls may cause an intense double slope effect. It is characterized by rapid initial and slow late decays, thus the decay curve exhibits so-called a “sagging” appearance. It was found also that a phenomenon of mode localization is an important factor in modifying the double slope sound decay.